Mining coal and undermining gender : rhythms of work and family in the American West - Rolston, Jessica Smith, 1980- (Rutgers University Press, 2014)
Among the miners of Wyoming's Powder River Basin-the largest coal-producing region in the U.S.-anthropologist Jessica Smith Rolston reveals how the mining industry, though heavily masculinized, generates new configurations of the "working family"--A kind of kinship based on the shared burdens of shift work and concerns for safety, which challenges and reproduces gender differences in everyday working and family life